Multiple Regions Drive Hepatitis Delta Virus Proliferation and Are Therapeutic Targets - Zi, Jun; Gao, Xiuzhu; Du, Juan; Xu, Hongqin; Niu, Junqi; Chi, Xiumei (Frontiers in Microbiology, 2022)
Hepatitis Delta Virus (HDV) is the smallest mammalian single-stranded RNA virus. It requires host cells and hepatitis B virus (HBV) to complete its unique life cycle. The present review summarizes the specific regions on hepatitis D antigen (HDAg) and hepatitis B surface antigen (HBsAg) that drive HDV to utilize host cell machinery system to produce three types of RNA and two forms of HDAg, and hijack HBsAg for its secretion and de novo entry. Previously, interferon-α was the only recommended therapy for HDV infection. In recent years, some new therapies targeting these regions, such as Bulevirtide, Lonafarnib, Nucleic acid polymers have appeared, with better curative effects and fewer adverse reactions.